Alih Kode dan Campur Kode Pada Album Lagu “Sounds Of Java” Karya Eka Gustiwana di Spotify - Wulandari, Wulandari; Latif, Abdul (Jurnal Ilmiah Wahana Pendidikan, 2024)
Code-switching and code-mixing is a change in language use or from a particular language variety to another. And in communicating even now, many use code mixing and code switching. The song is also a communication between musicians and listeners. And now songs are also commonly heard on social media, one of the social media that provides to be able to listen to songs is spotify. Spotify is a platform technology that provides many songs that can be heard by everyone. The song has also used a lot of code switching and code mixing and can already be heard on social media such as spotify. But many musicians or even the public do not know what code mixing and code switching is like. Therefore, the purpose of this research is to find out the code switching and code mixing of the album of songs by Eka Gustiwana entitled "Sounds of Java". The method used in this study is a qualitative method with content analysis techniques. The data obtained from the album "Sounds of Java" contained 15 code switching and 4 code mixing. And it can be concluded that the album "Sounds of Java" by Eka Gustiwana uses a lot of code switching in making the song.